An Efficient Method for Adventitious Root Induction from Stem Segments of Brassica Species - Srikanth, Sandhya; Choong, Tsui Wei; Yan, An; He, Jie; Chen, Zhong (Frontiers in Plant Science, 2016)
Plant propagation via in vitro culture is a very laborious and time consuming process. The growth cycle of some of the crop species is slow even in the field and the consistent commercial production is hard to maintain. Enhanced methods of reduced cost, materials and labour significantly impact the research and commercial production of field crops. In our studies, stem-segment explants of Brassica species were found to regenerate adventitious roots (AR) in aeroponic systems in less than a week. As such, the efficiency of root regeneration from stem explants of six cultivar varieties of Brassica spp were tested without the use of any plant hormones. New roots and shoots were regenerated from Brassica alboglabra (Kai Lan), Brassica oleracea var. acephala (purple kale), Brassica rapa L. ssp. Chinensis L (Pai Tsai, Nai Bai C and Nai Bai T) explants after 3 to 5 days of growing under 20±2°C cool root zone temperature (C-RZT) and 4 to 7 days in 30±2°C ambient root zone temperature (A-RZT). However, Brassica rapa nipposinica (Mizuna) explants were only able to regenerate in C-RZT. All regenerated explants were able to develop into whole plants, with higher biomass obtained from plants that grown in C-RZT. Moreover, explants from both RZTs produced higher biomass than plants grown from seeds (control plants). Regeneration efficiency was affected by RZTs and explant cuttings of donor plants. Photosynthetic CO2 assimilation rate (Asat) and stomatal conductance (gs sat) were not significantly differentiated between plants derived from seeds and explants at both RZTs. As such, this method of regeneration using aeroponics is suitable for all commercial cultivars studied. The findings of this study could be applicable in the mass propagation of vegetable crops, shortening the growth cycle as seed germination and seedling development periods can be eliminated.